A three-dimensional fractional visco-hyperelastic model for soft materials. (January 2023) - Gao, Yunfei; Yin, Deshun; Tang, Mao; Zhao, Bin
Abstract: Soft materials have attracted widespread attention and brought a wave of novel potential applications. Accurate mechanical characterization is crucial for improving the ration design of the desired soft elements and understanding the influence of deformation properties on themselves. However, the intrinsic complexity of mixed elasticity and viscosity in terms of their material property, posing new challenges for constitutive modeling. In this work, a fractional visco-hyperelastic constitutive model is developed by introducing the fractional viscoelasticity into finite strain: two branches are incorporated where a hyperelastic spring is used to describe the equilibrium response, and a non-linear fractional dashpot is introduced to characterize the time-dependent material response by employing the 3D fractional viscoelasticity. It provides a method from the perspective of fractional mechanics to avoid the increased number of governing equations and the associated complex calibration process caused by introducing the internal variables. The results show that the proposed model can successfully describe the rate dependent mechanical behavior of soft materials as well as predict the material behavior in different deformation modes with reasonable accuracy.